Genetic profiling of basal cell carcinomas detects postzygotic mosaicism in basal cell naevus syndrome. (5th December 2018) - Reinders, M.G.H.C.; Cosgun, B.; Gijezen, L.M.C.; van Oosterhoud, C.N.; Kelleners‐Smeets, N.W.J.; Vermander, E.; Vreeburg, M.; Steijlen, P.M.; Mosterd, K.; van Geel, M.
Summary: Basal cell naevus syndrome (BCNS) is associated with germline mutations in the PTCH1 gene. Postzygotic mosaicism can also cause BCNS. Here we describe two patients, one with multiple basal cell carcinomas (BCCs) and one with clinical BCNS, who had no PTCH1 mutation in DNA extracted from blood. In both patients, we performed genetic analysis on different BCCs, revealing the presence of a shared PTCH1 mutation in all tumours. Our findings show that in patients with symptoms of BCNS and initial absence of a PTCH1 mutation in blood, genetic profiling of BCCs can detect postzygotic mosaicism. What's already known about this topic? Basal cell naevus syndrome (BCNS) is associated with germline mutations in the PTCH1 gene, but it can also be caused by low‐grade postzygotic mosaicism in PTCH1 . What does this study add? In patients suspected of having BCNS or patients with multiple basal cell carcinomas (BCCs) with a special distribution on the body and no mutation detected in blood, it is worthwhile to search for a shared PTCH1 mutation in their BCCs as this can detect postzygotic mosaicism. This information is important to ensure proper surveillance programmes, choose the right therapy and provide adequate genetic counselling. Abstract : Linked Comment : Torrelo. Br J Dermatol 2019; 181 :447–448 . Plain language summary available online